Study of Microorganisms Associated with Spoilage of Onions Sold in Mbiama Market, Rivers State, South South Nigeria - Imarenezor Edobor Peter Kenneth; Opara Christiana Ngozi; Efere Yarwadum Samson (Darul Yasin Al Sys, 2026)
Onions are a staple vegetable in many Nigerian households, and their spoilage can contribute to significant economic losses and food insecurity. This study investigated the microorganisms associated with the spoilage of onions sold in Mbiama Tuesday Market, Rivers State, South-South Nigeria, and examined their potential implications for public health. A total of 100 onion samples were collected, and the associated microorganisms were isolated, identified, and characterized using standard bacteriological and mycological techniques, including biochemical testing and antibiotic sensitivity assays. The results showed that the onions were contaminated with a variety of bacteria—Bacillus spp., Pseudomonas spp., Staphylococcus spp., and Escherichia coli—and fungi, including Mucor, Aspergillus niger, yeast, and Penicillium spp., all of which were capable of causing soft rot, discoloration, and decay. Among the bacterial isolates, E. coli was the most frequent (23.5%), whereas Pseudomonas spp. was the least frequent (9.8%); among the fungi, A. niger was the most frequent (13.7%) and Mucor the least frequent (5.9%). Bacterial colony counts ranged from 5.2 × 10⁵ CFU/g (E. coli) to 5.6 × 10⁵ CFU/g (Pseudomonas spp.), while fungal counts ranged from 1.4 × 10⁵ CFU/g (yeast) to 1.58 × 10⁵ CFU/g (A. niger). Biochemical tests revealed that Bacillus spp. and Staphylococcus spp. were catalase and coagulase positive, whereas Pseudomonas spp. and E. coli were coagulase negative. Antibiotic sensitivity testing showed that Staphylococcus spp. was resistant to the tested antibiotics, while Bacillus spp., E. coli, and Pseudomonas spp. remained sensitive. The study concludes that onions sold in Mbiama Market are contaminated with diverse spoilage-causing bacteria and fungi, posing a potential risk to public health. These findings underscore the need for proper handling, storage, and preservation practices, such as maintaining cool, dry storage conditions and ensuring hand hygiene among vendors and consumers as well as further research to develop effective strategies for controlling microbial spoilage of onions in Nigeria.